How Primary School Students Perceive Primary School Teacher Exchange? - Erol, Mustafa; Basaran, Mustafa (ANI PUBLISHING, 2020)
The aim of this study is to determine how the changing of the primary school teacher affects the students. Method of research is qualitative research. Semi-structured interview and content analysis techniques were used for data collection and processing. The study conducted in a public primary school in Istanbul in the academic year of 2017-2018. To determine the study group criterion sampling technique that is among the purposeful sampling methods was used. The collected data were evaluated by content analysis and the thoughts of the students about the changing of primary school teachers were identified. As a result of the analyzes, the students feel sad due to the changing of teachers and feel like they have started school again. The metaphors they use are emphasized to change and depletion. In addition, it has been observed that the changing of primary school teacher has a negative effect on students' perception of teachers.
Keywords: Primary school teacher; primary school teacher exchange; paid and contracted teaching; PERCEPTIONS; Education & Educational Research